Pedagogical experience of the teaching methodology on the educational processes. - Obid, Nabiev; Gavkhar, Juraeva; Mardonovna, Turdieva Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates major points of the different teaching methods in educational purposes. On this case, improved experiences of the reputable teachers from well-known HEIs were analyzed both theoretically and methodologically in order to lead better implementations as the whole. The article substantiates the feasibility of using the design methodology for pedagogical cases, while illustrating better experiences of improved systems to get better efficiency and interests in further. Finally, research has concluded with both outcomes and shortcoming of the issue with the relevant recommendations for the upcoming investigations.